TAXONOMY, ECOLOGY AND DISTRIBUTION OF REPRESENTATIVES OF THE FAMILY ENIDAE WOODWARD, 1903 IN THE KOHITAN MOUNTAIN - Juraeva Samiya Hasanovna; Bobokeldieva Shakhnoza Abdusamatovna; Khujanova Nigora Boymurat kizi (American Journal Of Agriculture And Horticulture Innovations, 2023)
In this article, the diversity of land molluscs of Kohitang was studied. Malacafauna with 4 species belonging to 3 genera were described in the Kohitang mountain range and explored the unexploited lands of desert hilly mountain regions